DESTRUCTIVENESS OF HUMAN BEHAVIOR: PHILOSOPHICAL ANALYSIS - Shapoval, N. V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
Despite the obvious successes of modern Western civilization, the suppression of the individual by society continues to be a serious problem, as well as the tension that is turning into an open confrontation between the individual and society. Having existed in human society since the beginning of history, in our time this confrontation is especially acute in the destructive behavior of individuals. The article analyzes various forms of human destruction, its causes and abstruse reasons. Constructive and destructive manifestations of human behavior are considered in relation to the biological and psychological characteristics of person, social relations, as well as his spiritual nature.